Socio-economic impact of Soil Health Card scheme in the state of Andhra Pradesh - H, ANKHILA R; SINGH, ALKA; KUMAR, PRAMOD; KUMAR, SURESH; MEENA, M C; SINGH, RASHMI; SUNANI, SUNIL KUMAR; ADHIKARY, PARTHA PRATIM; KUMAR, DINESH; PRADHAN, SANATAN; H, SUNIL B (The Indian Journal of Agricultural Sciences, 2023)
The study is an attempt to evaluate the effectiveness of the soil health card (SHC) scheme in Andhra Pradesh (AP). Primary survey in the two selected districts of the AP state was carried out during 2020. Data set has 120 SHC adopters and 60 non-adopters of SHC from Chandragiri, Chittecherla blocks of Chittoor and Allur, Nellore blocks of Nellore district of Andhra Pradesh. The study evaluated the factors affecting the adoption of SHC in the selected districts of AP. Among them, number of trainings attended, membership of farmer organizations, the timely extension service availability has shown positive impact on adoption of SHC. However, distance to input market, age, and family size had significant negative impact on adoption of SHC. Impact of SHC showed significant decline in use of nitrogen and phosphorus nutrients by 20 kg/ha and 19 kg/ ha, respectively, among the adopters. Micronutrient usage increased by 9.15 kg/ha among the adopters of SHC. The study implies SHC scheme has reduced the excess usage of fertilizers in paddy cultivation in the survey area. It also recommends timely extension service to improve fertilizer savings by farmers.